Mucormycosis and COVID-19: a lethal combination - Emmanuel Zayas Fundora; Carlos Enrique Salgado Fuentes (Universidad de Ciencias Médicas de Granma, 2022)
Dear Editor: Mucormycosis is an angioinvasive infection caused by fungi of the order Mucorales. It is the third most important invasive mycosis, after Candida spp. and Aspergillus spp. infections, which are opportunistic, severe and rapidly evolving infections. The most important genera are Rhizopus, Mucor, Absidia and Cunninghamella 1 , with R. arrhizus (also called R. oryzae) being the most commonly found in humans with an incidence of 50-60 % 2 . Mucormycosis fungal infection occurs normally in immunocompromised hosts under predisposing circumstances such as: diabetes, renal or hepatic failure, chemotherapy, therapy with immunosuppressive agents, neutropenia, leukemia, AIDS, tuberculosis, extensive burns, malnutrition, among others 2 , 3 . The global pandemic of coronavirus disease 2019 (COVID-19) has infected more than 18 million people internationally ( 3 . Caused by coronavirus-2 (SARS-CoV-2), the disease can progress to acute respiratory distress syndrome (ARDS), a condition that increases susceptibility to fungal pulmonary co-infections 4 . Several cases have been reported by dissimilar authors regarding the association between SARS-CoV-2 infection and mucormycosis fungal postinfection. Mekonnen ZK et al. 4 ) describe in their article a case of invasive fungal rhinosinusitis with orbital involvement in a patient with COVID-19 and discuss the prevalence of fungal coinfection with COVID-19, as well as the diagnostic and management challenges faced by critically ill patients. After confirmation of Covid infection this case underwent intranasal tissue culture extraction and biopsy because clinical and radiographic signs that were highly suspicious for acute invasive fungal invasive rhinosinusitis with orbital involvement were found in the orbits and neck following CT angiography of the brain, orbits and neck. Histopathology demonstrated the presence of mucormycosis with angioinvasion. As raised by Moorthy A et al. 5 in their study, the outbreak of mucormycosis cases in recovered COVID-19 patients in multiple centers in Bangalore city, India, during the last 6 months was of concern and was found to be clearly associated with treatment of the disease with corticosteroids. According to the authors, the incidence of the cases studied, qualifies as an epidemic of mucormycosis within the COVID-19 pandemic. COVID-19 infection contributes in multiple ways to this invasion through the immune dysregulation that manifests as a reduction in the number of T lymphocytes. T cells can alter innate immunity by increasing the propensity for secondary fungal infections. The pathogenesis of COVID-19 resembles the spectrum of thrombotic microangiopathy (TMA) causing angioinvasion and endothelial damage much like mucormycosis, which aggravates the disease 6 . Glucocorticoids have been widely used to reduce hospital stay and mortality related to COVID-19. Dexamethasone and methylprednisolone have been incorporated into most protocols in COVID-19 infection, especially in moderate to severe cases 7 . Due to the immunosuppressive nature of glucocorticoids, patients become more susceptible to secondary infections thus necessitating strict surveillance focused on early detection of this dangerous fungal infection in patients post COVID-19 infection. Based on the above, the principle of multidisciplinary care in the follow-up of these patients is reaffirmed. The important role played by health professionals in the identification and timely treatment of an infection that can cause irreversible damage and even death, and which is not always given the required importance, is revalidated.